Terpenoids and sterol from aphanamixis polystachya - Ragasa, Consolacion Y. (Animo Repository, 2014)
The dichloromethane extract of the air-dried leaves of Aphanamixis polystachya (Wall.) Parker afforded α-copaene (1), squalene (2), polyprenol (3), β-sitosterol (4), lutein (5), and β-carotene (6). The structure of 1 was elucidated by extensive 1D and 2D NMR spectroscopy and confirmed by mass spectrometry. © 2014, Journal of Chemical and Pharmaceutical Research. All Rights Reserved.